2019
DOI: 10.14209/jcis.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling of Brazilian In-Home PLC Channel Features

Abstract: This paper deals with the statistical modeling of key features of power line communication (PLC) channels that are necessary for designing data communication systems that operate over theses channels. The key features are average channel attenuation, root mean squared delay spread, coherence bandwidth and coherence time. All these features were estimated from in-home PLC channels measured in seven distinct Brazilian residences. Assuming that each feature is a random variable, four criteria (i.e., maximum likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The curves of the scattering parameters, which are measured between the adaptive PLC coupling circuits, were performed in a 127 V rms 60 Hz electric power circuit with a power line of 15 meters in length and constituted by two parallel wires with 2.5 mm in diameter. The distance of 15 meters agrees with the distances observed in the average area of Brazilian apartments [46].…”
Section: Control Unitsupporting
confidence: 85%
“…The curves of the scattering parameters, which are measured between the adaptive PLC coupling circuits, were performed in a 127 V rms 60 Hz electric power circuit with a power line of 15 meters in length and constituted by two parallel wires with 2.5 mm in diameter. The distance of 15 meters agrees with the distances observed in the average area of Brazilian apartments [46].…”
Section: Control Unitsupporting
confidence: 85%
“…The table also compares the ACA values with those that exist in literature from other countries [13], [37]. From table 2, it can be observed that all the three statistical parameters -maximum, minimum and mean values of the ACA for Nigerian PLC channel are higher than what is obtained in Brazil and Spain.…”
Section: Statistical Measurement Of the Average Attenuation On The Plc Channelmentioning
confidence: 76%
“…Also, analysis of the ACG, RMS-DS and CB for the upper frequency edge of 300 MHz was carried out in Spain in [11]. In [12] and [13], extensive measurement campaign and numerical analysis of the ACG, RMS-DS and CB parameters for the Brazilian in-home power line channel were presented. In this research work, the results of preliminary measurements on the Nigerian indoor PLC channel are presented.…”
Section: Introductionmentioning
confidence: 99%